2015
DOI: 10.3109/0284186x.2015.1027411
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of planar bone scintigraphy, SPECT, SPECT/CT, 18F-NaF PET/CT and whole body 1.5T MRI, including DWI, for the detection of bone metastases in high risk breast and prostate cancer patients: SKELETA clinical trial

Abstract: wbMRI+DWI showed similar diagnostic accuracy to (18)F-NaF PET/CT and outperformed (99m)Tc-HDP SPECT/CT, and (99m)Tc-HDP BS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
120
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(134 citation statements)
references
References 21 publications
8
120
1
5
Order By: Relevance
“…Another study showed better specificity but lower sensitivity for detection of bone metastases from PC with 11 C-choline-PET/CT compared to BS (19). Whole-body MRI with diffusion-weighted imaging and [ 18 F] fluoride-PET/CT have also proved superior to BS in high-risk PC (20), suggesting that more appropriate methods are available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed better specificity but lower sensitivity for detection of bone metastases from PC with 11 C-choline-PET/CT compared to BS (19). Whole-body MRI with diffusion-weighted imaging and [ 18 F] fluoride-PET/CT have also proved superior to BS in high-risk PC (20), suggesting that more appropriate methods are available.…”
Section: Discussionmentioning
confidence: 99%
“…BS has in previous publications been outperformed by PET/CT (19,20). Therefore, we chose not to use BS as the standard of reference.…”
Section: Methodsmentioning
confidence: 99%
“…The authors drew attention to the lower availability and higher cost of PET/CT versus SPECT/CT for a routine check-up 34 . Jambor 35 and Hahn 37 reported about a slight increase in the proportion of indeterminate lesions on the PET/CT scans for the detection of bone metastases in high risk breast cancer patients. For this reason, some authors subsequently recommended the deployment of PET/CT for uncertain findings on SPECT/CT skeleton, even in the form of a Na 18 F-18 FDG PET/CT "cocktail" (ref.…”
Section: Comparison With Hybrid Systems Using Petmentioning
confidence: 99%
“…However, data on comparisons of these methods with PET methods to determine the best technique for current clinical practice or for clinical trials are insufficient. There are early data supporting the use 18F-FDG PET/MRI (include diffusion weighted imaging) to assess malignant disease in the skeleton, with the possibility of taking advantage of the synergies offered by combining morphologic, physiologic and metabolic imaging 34,35 .…”
Section: Comparison With Hybrid Systems Using Petmentioning
confidence: 99%
See 1 more Smart Citation